Given information :
G = 173.3 KJ
H = 180.7 KJ
T = 303.0 K
S = unknown (?)
By using the given formula : G = H - TS , we can calculate the value of 'S'
On rearranging the formula we get : S =
![(H-G)/(T)](https://img.qammunity.org/2019/formulas/chemistry/high-school/t2x61gxwhdyqvsnl8bcnuxe5hagu9139in.png)
Plug in the value of G , H and T in the above formula :
S =
![((180.7 KJ - 173.3KJ))/(303.0K)](https://img.qammunity.org/2019/formulas/chemistry/high-school/34dba6jdqo06wyjct9pybb63mjo6j1y54n.png)
S = 0.02442
![(KJ)/(K)](https://img.qammunity.org/2019/formulas/chemistry/high-school/wobr2yinzrnxyhsymijeu5p88zah2a1ltw.png)